Jigsaw Strategy on Learning Outcomes and Higher Order Thinking Skills of Students in Social Science at Madrasah Tsanawiyah - Fadilla Syahriani; Ferdi Yufriadi; Awis Alhkarni; Meisya Anggraini Rizki; Nadyya Zahratul Jannah; Valensius Ngardi; Tri Wibowo (AL-ISHLAH: Jurnal Pendidikan, 2025)
Innovative teaching strategies are essential for improving student learning outcomes and developing Higher Order Thinking Skills (HOTS). This study examines the effectiveness of the Jigsaw learning strategy in enhancing students’ critical thinking, analytical abilities, and problem-solving skills in Social Science at MTsS Ashhabul Yamin Lasi. A quasi-experimental design was used, involving two groups: an experimental group that implemented the Jigsaw strategy and a control group that followed conventional teaching methods. Data were collected through pretests and posttests, incorporating multiple-choice and descriptive tests to assess both learning outcomes and HOTS. Statistical analysis included correlation techniques and simple regression, processed using SPSS version 2.6. The study sample comprised eighth-grade students, selected from the total student population at the school. The research process included three phases: pretest, Jigsaw strategy implementation, and posttest. The findings indicate that students in the Jigsaw group demonstrated significant improvements in learning outcomes and HOTS compared to those in the control group. The strategy fostered collaborative learning, enhancing students’ ability to think critically, analyze concepts, and solve problems more effectively. The results suggest that the Jigsaw learning strategy is a valuable pedagogical tool for promoting student engagement and cognitive development. Its application in Social Science education provides insights into improving teaching effectiveness in secondary schools. This study highlights the positive impact of collaborative learning on student performance and supports the broader implementation of student-centered teaching approaches. The findings offer practical implications for enhancing educational strategies globally.